PENGELOLAAN APBN DAN POLITIK ANGGARAN DI INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - AAN JAELANI (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
The development policy in the reformation era gives priority to the paradigm of human development that puts people as the development actors and places local economy as a vehicle for community welfare. However, the government policy as stated in the national budget precisely contradicts with the role of government that should create the community welfare. This study uses the qualitative approach by using historical and verstehen methods. The management of the national budget shows the existence of the government's role in regulating the sources of general revenue and expenditure budget. The practices of the state financial management used for development purposes to create the public welfare have been conducted since the time of Prophet Muhammad. The management of the national budget in the reformation era uses performance-based budget structure that aims to improve the performance of government with good governance that requires the effectiveness, efficiency, transparency, and accountabilicy in its management. However, the abuse of the budget in the form of corruption still occurs in the management of this national budget. Key words: National Budget, Budget-Politics, Corruption, Islamic Economy.